Futile care: why Intensive care nurses’ provide it?A phenomenologic study - Yekefallah, leili; Ashktorab, tahereh; Manoochehri, houman; alavi majd, hamid (Advances in Nursing & Midwifery, 2015)
Background: futile care is provided in intensive care units for multiple reseans.for decline such care awareness of effective factors associated to providing futile care is nessecarry. This research reports, experience of intensive care nurses of resaens for providing of futile care . Methods: In this qualitative study, a phenomenological approach was used. We used semi structured and indepth interviews of purposive sample of25 intensive care unit nurses’ in all hospitals in Qazvin to identify codes and categorize themes in the data. Results: three themes emerged from the data were as follows: 1-personal beilief and value, 2-policy of institute, 3-socio-cultural factors. Conclusion: The results demonstrate that reseans for providing of futile care in intensive care unit is different and personal beilief, environment and organizational restrictions influences the development of the futile care and presents barriers to achieving an ideal care. Therefore nursing leaders must reduce futile care among nursing in intensive care. Experiences of futile care in intensive care units reflect on nurses’ patient care negatively, increases their burnout, and reduces their job satisfaction. Therefore nursing leaders must reduce futile care among nursing in intensive care. Keywords: futile care- effective factors- Intensive care nurses- experience - phenomenology